Official guide for GMAT verbal review, 2015 (John Wiley, 2014)
This is the only official study guide focusing on the verbal portion of the GMAT exam. It delivers more than 300 retired GMAT® questions and answer explanations from the creators of the test to help focus your test preparation efforts. New to The Official Guide for GMAT® verbal Review 2015: Online access to 300 Reading Comprehension, Critical Reasoning, and Sentence Correction questions allowing the creation of customized practice tests. Exclusive access to videos from real test takers and GMAC staff who share insight and tips on GMAT® preparation.